Effect of laser processing microstructure on the bonding strength and failure mode of 7075-T6 aluminum alloy adhesive joints. (June 2021) - Zhang, Chong; Chen, Lingyu; Zhang, Yongkang; Wang, Guan; Jin, Jie
Abstract: The strength of adhesive joints of aluminum (Al) alloys can be enhanced by laser surface treatment. In this study, a nanosecond fiber laser was used to process crater array (CA), multi-groove (MG), and crater-array–multi-groove (CA–MG) microstructures on 7075-T6 Al alloy substrates. The shear strength ( σ ) was measured by a single-lap shear test. For the CA microstructure, how the pulse energy ( E ) and crater overlap rate ( δ ) affect σ was studied. For the MG and CA–MG microstructures, how E and the groove distance ( H ) affect σ was studied. Also, the mechanism by which the characteristic parameters of each microstructure affect σ was compared through the failure mode. The results show that when δ  = 30 %, the CA microstructure is the most conducive for improving the shear strength; however, regardless of the choice of E and δ, the CA microstructure leads to cohesive failure in part of the bonding region. The MG microstructure leads to cohesive failure in the entire bonding region only when H  = 0; when H  = 40 or 80 μm, the region outside the grooves is prone to adhesive failure. Regardless of the choice of E and H, the CA–MG microstructure formed by two-step laser processing leads to cohesive failure in the entire bonding region. From the perspective of improving efficiency and saving energy, E  = 880 μJ and δ  = 30 % should be selected for processing the CA microstructure and E  = 176 μJ and H =80 μm should be selected for processing the MG microstructure.